Determination of the efficiency of the gas-pumping unit of the compressor station according to the data of its operation - Андріїшин, Михайло Петрович; Капітанчук, Костянтин Іванович; Андріїшин, Назар Михайлович (Science-based technologies, 2021)
For the first time, the article analyzes the efficiency of the booster compressor station's TCU based on the data of its operation based on the gas-dynamic processes that take place in the gas compressor impeller. The limiting modes and the possibility of work of a multistage booster compressor station of a gas field at a late stage of its operation at low reservoir pressures have been determined, which makes it possible to carry out a set of measures for the choice of equipment and modes of work TCU. The implementation of the measures makes it possible to minimize the negative impact work of TCU on the environment and to optimize the material and monetary costs of natural gas transportation. On the basis of the presented algorithm, a method has been developed for calculating the efficiency of the gas-pumping equipment of the second stage of a compressor station, which pumps natural gas from a group of gas fields at a late stage of their operation into the main gas pipeline. As an approbation of the proposed methodology, the dispatching data of the second stage of the compressor station in two versions: operation with one and with two gas compressor units are considered. The calculation results are presented in tables. It is concluded that, regardless of the fact that the inlet pressure is low, and the flow path of the gas compressor is seven-stage, the work of friction forces and the work of thermal forces in the impeller of the gas compressor are relatively small relative to the value of adiabatic work, which is directly used to compress natural gas. The design and geometrical dimensions, the number of blades for each stage of the gas compressor, based on the operating conditions, are well chosen. The indicator efficiency of the gas compressor is 71%. The fuel gas consumption of the blower drive for pumping 1000 m3 is 17 m3. During the operation of a compressor station with two gas compressor units, the productivity of one compressor decreased to 75 thousand m3 / hour with an average productivity of the compressor station of 150 thousand m3 / hour. In this case, the gas compression ratio increased to ε = 3.2, and the polytropic index decreased from 1.44 to 1.34. The work of the frictional forces and the work of thermal forces are even smaller in comparison with the adiabatic work, and the indicator efficiency of the gas compressor increased to 85%. Therefore, the operation of a compressor station with two TCU is more efficient than with one. However, the fuel gas consumption of the blower drive for pumping 1000 m3 when the compressor station operates with two TCU is 23 m3, and the effective power on the blower shaft is 3750 kW, which is much less than the nominal value. This means that efficient operation of two blowers in parallel is impossible due to insufficient productivity of the natural gas field. This increases the consumption of fuel gas, which leads to an increase in emissions of carbon dioxide into the atmosphere. Therefore, for the effective operation of the compressor station, it is necessary to reconstruct the first stage in order to increase its productivity, to increase the working pressure at the inlet to the compressor of the second stage of the booster compressor station